2019
DOI: 10.4093/dmj.2018.0218
|View full text |Cite
|
Sign up to set email alerts
|

Early Assessment of the Risk for Gestational Diabetes Mellitus: Can Fasting Parameters of Glucose Metabolism Contribute to Risk Prediction?

Abstract: Background: An early identification of the risk groups might be beneficial in reducing morbidities in patients with gestational diabetes mellitus (GDM). Therefore, this study aimed to assess the biochemical predictors of glycemic conditions, in addition to fasting indices of glucose disposal, to predict the development of GDM in later stage and the need of glucose-lowering medication. Methods: A total of 574 pregnant females (103 with GDM and 471 with normal glucose tolerance [NGT]) were included. A metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
1
28
0
3
Order By: Relevance
“…Li et al recently reported results of their study which included 2112 pregnant women and concluded that a fasting glucose concentration over 4.5 mmol/L during the first trimester offers optimal specificity and sensitivity for GDM prediction ( 28 ). The fasting plasma glucose concentration was more accurate than other traditional risk factors, such BMI or age, when used for GDM prediction, but it was less accurate than OGTT testing ( 25 , 26 , 29 ).…”
Section: Conventional Predictive Gdm Biomarkersmentioning
confidence: 87%
See 1 more Smart Citation
“…Li et al recently reported results of their study which included 2112 pregnant women and concluded that a fasting glucose concentration over 4.5 mmol/L during the first trimester offers optimal specificity and sensitivity for GDM prediction ( 28 ). The fasting plasma glucose concentration was more accurate than other traditional risk factors, such BMI or age, when used for GDM prediction, but it was less accurate than OGTT testing ( 25 , 26 , 29 ).…”
Section: Conventional Predictive Gdm Biomarkersmentioning
confidence: 87%
“…Existing international guidelines recommend testing for pregestational diabetes in women in early pregnancy with body mass index (BMI) > 30 kg/ m 2 , impaired glucose tolerance, and a history of GDM (7). (25,26,29).…”
Section: Diagnosis Of Gdmmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is defined as the existence of impaired glucose metabolism in pregnancy and is associated with high adverse health risks to both the mother and child [1][2][3][4]. In the Hyperglycemia and Adverse Pregnancy Outcomes study, the risk of adverse maternal, fetal, and neonatal outcomes increased with progressive hyperglycemia, even with no clear inflection points [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent prediction models for GDM have been developed using conventional regression analyses [17][18][19]. However, machine learning, a data analysis technique that develops algorithms to predict outcomes by "learning" from data, is increasingly emphasized as a competitive alternative to regression analysis.…”
Section: Introductionmentioning
confidence: 99%